Tabayyun Morals in the Qur'an: Analysis of Maqasidi's Tafsir on Tabayyun Verses - Isna Quffa Awamira; Ikhwanudin Ikhwanudin; Muhammad Nur Amin (al-Afkar, Journal For Islamic Studies, 2026)
Advances in information technology in the digital age have given rise to various ethical issues in communication, such as the spread of hoaxes, misinformation, and hate speech. These phenomena underscore the importance of applying the principle of information verification in social life. This study aims to examine the concept of akhlak tabayyun in the Qur’an through a maqasidi exegetical approach, as well as to explain its urgency in the formation of communication ethics. This study employs a qualitative method using a literature review approach, with the Qur’an and exegetical works as primary sources, supplemented by relevant scholarly literature. The results of the study indicate that tabayyun is not merely understood as a technical verification process but also as an ethical principle oriented toward the objectives of Islamic law (maqasid al-syari‘ah), such as safeguarding reason, dignity, and social stability. Therefore, the internalization of the values of tabayyun has become a fundamental necessity in facing the overwhelming flow of information in the digital age.